THE PHILOSOPHICAL ROLE OF COLORING IN THE PERSPECTIVE OF RAJASTHANI MINIATURE: राजस्थानी लघुचित्रो के परिप्रेक्ष्य में रंगो की दार्शनिक भूमिका - Kodode, Ujjwal (International Journal of Research -GRANTHAALAYAH, 2014)
In Rajasthan, the interest towards painting and its original form was traditionally prevalent. The credit for reviving Rajasthani traditions and cultures is seen in the traditional painting here, in the depiction of women and the expression of colors. Evidence of this is seen in the lineages and color combinations etched in ancient times in the rock shelters here. There is an initial depiction by Rangay showing the expressions of the then figures. Rajasthani painting certainly occupies an important place in Indian art from the 16th century to the 19th century. The combination of colors is the predominance of this style. The variety of colors with rankhako has been skillfully perfected, but the simple combination of colors has been expressive, dynamic, strong and figurative. राजस्थान में चित्रकला प्रति अभिरूचि और उसका मौलिक स्वरूप परम्परागत रूप से प्रचलित था। जो राजस्थानी परम्परा एवं संस्कृतियों को गैारवान्वित करने का श्रेय यहां की पारम्परिक चित्रकला में नारी चित्रण और रंगांे की अभिव्यक्ति में दिखाई देता है। इसका प्रमाण यहां के शैलाश्रयों में प्राचीन काल में उकेरे गये रेखाकंन एवं रंग संयोजन में दिखाई पड़ता है। रंगांे द्वारा तत्कालीन आकृतियों के भाव दर्शा ने का प्रारंभिक चित्रण हुआ है। 16 वीं शताब्दी से 19 वीं शताब्दी तक राजस्थानी चित्रकला निश्चय ही भारतीय कला में महत्वपूर्ण स्थान प्राप्त है। रंगों का संयोजन रेखाओं का बारीकी इस शैली की प्रधानता रही है। रेंखाकनो के साथ रंगों की विभिन्न छंटा कुशलतापुर्ण, किन्तु सरल संयोजन, रंगों का अभिव्यक्तिपूर्ण,गतिशील, सशक्त एवं आलंकारिक किया गया है।